2021
DOI: 10.3390/nano11092355
|View full text |Cite
|
Sign up to set email alerts
|

Self-Sensing Cementitious Composites: Review and Perspective

Abstract: Self-sensing concrete (SSC) has been vastly studied for its possibility to provide a cost-effective solution for structural health monitoring of concrete structures, rendering it very attractive in real-life applications. In this review paper, comprehensive information about the components of self-sensing concrete, dispersion methods and mix design, as well as the recent progress in the field of self-sensing concrete, has been provided. The information and recent research findings about self-sensing materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 107 publications
(290 reference statements)
1
12
0
Order By: Relevance
“…Although not significantly contributing to the conductivity, the addition of fibers was effective in mitigating damage to the conductive network caused by the extension of cracks. The test results also showed that the recovery rate of resistance variation was higher than that of the normal concrete group when the specimens exceeded the compressive failure strength, which is consistent with previous studies by Ding et al [26] and Bekzhanova et al [27].…”
Section: Resistivity Coefficient Obtained Using Direct Current (Dc) L...supporting
confidence: 91%
See 2 more Smart Citations
“…Although not significantly contributing to the conductivity, the addition of fibers was effective in mitigating damage to the conductive network caused by the extension of cracks. The test results also showed that the recovery rate of resistance variation was higher than that of the normal concrete group when the specimens exceeded the compressive failure strength, which is consistent with previous studies by Ding et al [26] and Bekzhanova et al [27].…”
Section: Resistivity Coefficient Obtained Using Direct Current (Dc) L...supporting
confidence: 91%
“…It shows that adding K fibers to conductive concrete can reduce the speed at which cracks develop within concrete. The use of fibers can significantly reduce the trend of increasing resistivity [27] and has great potential for monitoring fatigue damage in different concrete structures [46].…”
Section: Resistance Variation During Cyclic Loading Testmentioning
confidence: 99%
See 1 more Smart Citation
“…If the stresses in the structural element is known, its life expectancy can be easily calculated using the simple beam theory [6]. The non-intrinsic sensors is based on utilizing external sensing devices such as: strain gauges, fiber optic sensors, and piezoelectric sensors [7]. While the intrinsic sensors are based on enhancing the self-sensing capabilities of the material.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the following tasks are considered: environmental protection, involvement of waste in the production of building materials to reduce the consumption of cement and improve the economic performance, improving the quality of building materials, including their operational resistance and durability, creation of waste-free technologies to produce building materials. Furthermore, the structural health monitoring techniques can investigate their condition to ensure the safety of the infrastructure during its service life [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%